Hubungan Komunikasi Seksual dalam Keluarga dengan Kecenderungan Perilaku Homoseksual Pada Santri - Rizqi Isnaeni Fajri; Muslimah Muslimah (Universitas Islam Bunga Bangsa Cirebon, 2020)
Nowadays the tendency of homosexual behaviour is more and more widespread, one of them is in Islamic boarding school. The tendency of homosexual behaviour in students has different characters in general, because they have a fluid nature, which sometimes appears and disappears in other times. Sexual communication in the family becomes important to be delivered to children, as family is the first environment that provides information about life. This study aims to examine the relationship between sexual communication in families and the tendency of homosexual behaviour in students. The research used quantitative method. The population of this study is Madrasah Aliyah Boarding School students, with the islamic boarding schools elected by random method from 12 schools and 3 schools was chosen to be the research sites, with total sample of 170 students. The research instrument uses the tendency of homosexual behavior scale, sexual communication in the family scale, which has been tested for its validation and reliability. Data analysis used multiple regression analysis with the help of SPSS 20.0 program. Based on this study there is a significant negative correlation between sexual communication in the family and the tendency of homosexual behavior in students, with a r_xy value of 0.005. From this study it can be concluded that the better sexual communication in the family is delivered the less the tendency for homosexual behavior occurs. Keywords: Sexual Communication in the Family; Trends in Homosexual Behavior; Students. Abstrak Dewasa ini kecenderungan perilaku homoseksual semakin marak, salah satunya di pondok pesantren. Kecenderungan perilaku homoseksual pada santri memiliki karakter yang berbeda pada umumnya, karena mereka memiliki sifat yang cair (fluid) yaitu kadang muncul, kadang hilang. Komunikasi seksual dalam keluarga menjadi penting yang harus diberikan pada anak, karena lingkungan pertama yang memberikan informasi tentang kehidupan. Penelitian ini bertujuan untuk menguji hubungan komunikasi seksual dalam keluarga dengan kecenderungan perilaku homoseksual pada santri. Metode penelitian yang digunakan adalah kuantitatif. Populasi penelitian ini adalah santri yang berada pada jenjang pendidikan Madrasah Aliyah pondok pesantren, pemilihn pondok pesantren dengan cara random dari 12 pondok pesantren lalu didapatkan 3 pondok pesantren untuk dijadikan tempat penelitian, dengan jumlah sampel sebanyak 170 santri. Instrumen penelitian menggunakan skala kecenderungan perilaku homoseksual, komunikasi seksual dalam keluarga, yang sudah dilakukan validasi dan reliabilitas. Teknik analisa data menggunakan analisis regresi ganda dengan bantuan program SPSS 20.0. Berdasarkan pada penelitian ini terdapat hubungan nilai negatif yang signifikan antara komunikasi seksual dalam keluarga dengan kecenderungan perilaku homoseksual pada santri, dengan nilai sebesar 0,005. Sehingga dalam penelitian ini dapat disimpulkan bahwa komunikasi seksual dalam keluarga semakin baik diberikan maka akan mengurangi kecenderungan perilaku homoseksual. Kata kunci: Komunikasi Seksual dalam Keluarga; Kecenderungan Perilaku Homoseksual; Santri.